What is the evidence that advertising policies could have an impact on gambling-related harms? A systematic umbrella review of the literature. (February 2023) - McGrane, E.; Wardle, H.; Clowes, M.; Blank, L.; Pryce, R.; Field, M.; Sharpe, C.; Goyder, E.
Abstract: Objective: To summarise the evidence on the impacts of gambling-related advertising that could lead to gambling-related harm, including impacts on vulnerable individuals and inequalities in the distribution of harms. Study design: An umbrella review of studies investigating the impact of gambling advertising. Methods: A review was undertaken of systematic reviews of qualitative, quantitative and mixed method studies reporting outcomes associated with gambling advertising and marketing. The search strategy included database searches (Web of Science, PsycInfo) and website searches. The quality of the included reviews was determined using A MeaSurement Tool to Assess systematic Reviews 2. Results: 1024 papers were identified by database searches. Eight systematic reviews, including 74 unique studies, met inclusion criteria. Included studies, using quantitative and qualitative methods, consistently support the existence of a causal relationship between exposure to advertising of gambling products/brands and more positive attitudes to gambling, greater intentions to gamble and increased gambling activity at both individual and population level. There is evidence of a 'dose–response' effect; greater advertising exposure increases participation which leads to a greater risk of harm. There was more evidence for the impact on children and young people and for those already at risk from current gambling activity with those most vulnerable more likely to be influenced. Conclusion: Gambling advertising restrictions could reduce overall harm and mitigate the impact of advertising on gambling-related inequalities. Public health harm prevention strategies should include policies which limit exposure to advertising, particularly among children and vulnerable groups.